Team sport in a COVID-19 world. A catastrophe in waiting, or an opportunity for community sport to evolve and further enhance population health? - Griffin, S. A.; Mendham, A.; Krustrup, P.; Murray, A.; Peirce, N.; Larkin, J.; Jaques, R.; Cowie, C. M.; Stokes, K. A.; Kemp, S. P. T. (British Journal of Sports Medicine, 2021)
While sporting governing bodies prepare guidelines and policies to comply with social distancing requirements and governmental guidelines, and some may feel that such changes threaten the very existence of their sport, is there a hidden opportunity to be found among the noise? Elite team sports generate significant financial wealth and widespread media attention, but grass-roots participation rates in many traditional team sports have been decreasing, especially over the last 5 years. This contrasts with some data suggesting that physical activity levels actually may be increasing overall across the general population, especially among women and older people. This begs the question, are sports losing touch with the general population, and are people turning to non-traditional sports and individual activities for leisure-time physical activity?